Pubertal Timing and Substance Abuse Treatment Outcomes: An Analysis of Early Menarche on Substance Use Patterns. Issue 6 (1st November 2016) - Hedges, Kristin; Korchmaros, Josephine D.
ABSTRACT: This article examines the influence of pubertal timing on substance use patterns, specifically the relationship between onset of menarche and onset of substance use and substance abuse treatment outcomes. Findings show a significant relationship between pubertal timing and age of onset of substance use and age of onset of substance use and substance use severity at intake into treatment. The article concludes with a call for further research into the possible relationship between pubertal timing and treatment outcomes as well as effective gender-specific interventions for prevention and treatment of substance abuse among adolescent girls.